Highly Reversible Zn Metal Anodes Enabled by Increased Nucleation Overpotential - Hu, Zhengqiang; Zhang, Fengling; Zhou, Anbin; Hu, Xin; Yan, Qiaoyi; Liu, Yuhao; Arshad, Faiza; Li, Zhujie; Chen, Renjie; Wu, Feng; Li, Li (Nano-Micro Letters, 2023)
Dendrite formation severely compromises further development of zinc ion batteries. Increasing the nucleation overpotential plays a crucial role in achieving uniform deposition of metal ions. However, this strategy has not yet attracted enough attention from researchers to our knowledge. Here, we propose that thermodynamic nucleation overpotential of Zn deposition can be boosted through complexing agent and select sodium L-tartrate (Na-L) as example. Theoretical and experimental characterization reveals L-tartrate anion can partially replace H2O in the solvation sheath of Zn2+, increasing de-solvation energy. Concurrently, the Na+ could absorb on the surface of Zn anode preferentially to inhibit the deposition of Zn2+ aggregation. In consequence, the overpotential of Zn deposition could increase from 32.2 to 45.1 mV with the help of Na-L. The Zn-Zn cell could achieve a Zn utilization rate of 80% at areal capacity of 20 mAh cm−2. Zn-LiMn2O4 full cell with Na-L additive delivers improved stability than that with blank electrolyte. This study also provides insight into the regulation of nucleation overpotential to achieve homogeneous Zn deposition. Highlights: 1 The nucleation overpotential was regulated by sodium L-tartrate to drive smaller critical size of Zn nucleus and accelerate the nucleation rate. 2 The L-tartrate anions and sodium ions can increase de-solvation energy barrier suitably and hinder the agglomerative Zn deposition resepectively. 3 Nucleation overpotential in modified electrolyte could increase from 28.3 to 45.9 mV, and high Zn utilization rate of 80% at current density of 10 mA cm−2 can be achieved.